Genomic Profiling of Parathyroid Carcinoma Reveals Genomic Alterations Suggesting Benefit from Therapy. (29th October 2018) - Kang, Hyunseok; Pettinga, Dean; Schubert, Adrian D.; Ladenson, Paul W.; Ball, Douglas W.; Chung, Jon H.; Schrock, Alexa B.; Madison, Russell; Frampton, Garrett M.; Stephens, Phil J.; Ross, Jeffrey S.; Miller, Vincent A.; et al.
Abstract: Background: Parathyroid carcinoma (PC) is a rare endocrine malignancy that can cause life‐threatening hypercalcemia. We queried whether comprehensive genomic profiling (CGP) of PC might identify genomic alterations (GAs), which would suggest benefit from rationally matched therapeutics. Methods: We performed hybrid‐capture‐based CGP to identify GAs and tumor mutational burden (TMB) in tumors from patients with this malignancy. Results: There were 85 total GAs in 16 cases (5.3 GAs per case), and the median TMB was 1.7 mutations per megabase (m/Mb), with three cases having >20 m/Mb (18.7%). The genes most frequently harboring GA were CDC73 (38%), TP53 (38%), and MEN1 (31%). All MEN1 ‐mutated cases also had loss of heterozygosity at that locus, but in contrast all CDC73 ‐mutated cases retained heterozygosity. GAs suggesting potential benefit from matched targeted therapy were identified in 11 patients (69%) and most frequently found in PTEN (25%), NF1 (12.5%), KDR (12.5%), PIK3CA (12.5%), and TSC2 (12.5%). A patient whose tumor harbored KDR T668 K and who was treated with cabozantinib experienced a > 50% drop in parathyroid hormone level and radiographic partial response of 5.4 months with duration limited by toxicity. Conclusion: CGP identified GAs in PC that suggest benefit from targeted therapy, as supported by an index case of response to a matched tyrosine kinase inhibitor. Moreover, the unexpectedly high frequency of high TMB (>20 m/Mb) suggests a subset of PC may benefit from immune checkpoint inhibitors. Abstract : Results from comprehensive genomic profiling in a cohort of patients with advanced parathyroid carcinoma are reported.